Discovery Blended Learning in Biology: Its Effectiveness on Self-Efficacy and Student Learning Outcomes in the New Normal Era - Elsa Listiani Cahya Ningsih; Ummi Nur Afinni Dwi Jayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
The limited face-to-face interaction has reduced school hours and resulted in students having difficulty understanding the lesson and completing assignments given by the teacher, and this caused a decline in learning outcomes. Optimizing the learning process in the new normal era will be effective by applying blended learning. One of the learning models that can support students is blended learning with discovery learning models. Through the discovery blended learning (DBL) model, students become more active in the learning process. This model can increase students' self-efficacy and collaboration with peers in the class because students feel confident and can solve a problem. This study aims to analyze the effectiveness of blended learning with discovery learning models on self-efficacy and learning outcomes in Biology subject during the new normal era. This research is a quasi-experimental research design with non-equivalent control of pretest-posttest group design. Data analysis was carried out by using the N-gain test and independent t-test. The results indicate that there is a significant difference in effectiveness in the class using DBL on student learning outcomes and self-efficacy with the control class using the conventional model. In DBL syntax, students' ability in formulating problems and finding concepts independently, and presenting results can help students improve learning outcomes and self-efficacy. The DBL model can be used as an alternative model to support students learning Biology at the high school level (SMA/MA) in Indonesia so that students are more active in discussions to solve problems related to the subject matter. This model is also expected to guide students to find concepts independently so that students become more confident and believe in their abilities, especially in the new normal era.